The Case for Cloud-Enabled Mobile Sensing Services - SEN, Sougata (Institutional Knowledge at Singapore Management University, 2012)
We make the case for cloud-enabled mobile sensing services that support an emerging application class, one which infers near-real time collective context using sensor data obtained continuously from a large set of consumer mobile devices. We present the high-level architecture and functional requirements for such a mobile sensing service, and argue that such a service can significantly improve the scalability and energy-efficiency of large-scale mobile sensing by coordinating the sensing & processing tasks across multiple devices. We then focus specifically on the problem of energy efficiency and provide early exemplars of how optimizing query execution jointly over multiple phones can lead to substantial energy savings.